2019
DOI: 10.1136/bmjopen-2018-025121
|View full text |Cite
|
Sign up to set email alerts
|

Associations between effort–reward imbalance and health indicators among school teachers in Chuquisaca, Bolivia: a cross-sectional study

Abstract: ObjectiveTo assess the association between effort–reward imbalance (ERI) and health indicators among Bolivian school teachers.DesignSchool-based cross-sectional study.SettingSixty randomly selected schools from rural (33) and urban (27) schools in Chuquisaca, Bolivia.ParticipantsA total of 1062 school teachers were invited to participate, of which 597 answered the questionnaire (response 56.2%).Exposure measurePsychosocial factors at work were explored through the short version of the Effort–Reward Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Health workers with poor sleep quality had higher levels of perceived effort, higher levels of perceived overcommitment, and higher ERI ratios than those with good sleep quality (Table 3 ). This finding is consistent with existing study findings [ 49 ]. Table 4 shows that the ERI ratio is the main risk factor for sleep disturbances in community health workers, and the same result was found for doctors and nurses.…”
Section: Discussionsupporting
confidence: 94%
“…Health workers with poor sleep quality had higher levels of perceived effort, higher levels of perceived overcommitment, and higher ERI ratios than those with good sleep quality (Table 3 ). This finding is consistent with existing study findings [ 49 ]. Table 4 shows that the ERI ratio is the main risk factor for sleep disturbances in community health workers, and the same result was found for doctors and nurses.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study showed that health workers with poor sleep quality had higher levels of perceived effort, higher levels of perceived overcommitment, and higher ERI ratios than those with good sleep quality (Table 3). This is consistent with existing research [43] . Table 4 shows that the ERI ratio was the main risk factor for sleep disturbances in community health workers (P = 0.000, OR = 34.334).…”
Section: Discussionsupporting
confidence: 94%
“…In a favorable case, for example, teachers’ high workload is compensated by adequate pay and appreciation by colleagues and students. According to this model, an effort-reward imbalance (ERI) generates psychosocial work stress that increases the risk of stress-associated illness and burnout in the medium and long term ( Van Vegchel et al, 2005 , Lehr et al, 2009 ; Zurlo et al, 2010 ; Wang et al, 2015 ; Rugulies et al, 2017 ; Solis-Soto et al, 2019 ; Madsen and Rugulies, 2021 ). In the study by Loerbroks et al (2014) , the ERI score in elementary school teachers was found to be a strong determinant not only of burnout but also of intention to leave the profession.…”
Section: Introductionmentioning
confidence: 99%